Sleep after intranasal progesterone vs. zolpidem and placebo in postmenopausal women – A randomized, double-blind cross over study. (June 2018) - Schüssler, P.; Kluge, M.; Adamczyk, M.; Beitinger, M.E.; Beitinger, P.; Bleifuss, A.; Cordeiro, S.; Mattern, C.; Uhr, M.; Wetter, T.C.; Yassouridis, A.; Rupprecht, R.; et al.
Highlights: After intranasal administration of the progesterone nasal gel MPP22 dose dependent sleep promoting effects were found in postmenopausal women. The spectral signature of MPP2 does not resemble sleep-EEG changes after GABA active compounds. Nocturnal progesterone levels increase after MPP22. Abstract: Context: The loss of progesterone during menopause is linked to sleep complaints of the affected women. Previously we demonstrated sleep promoting effects of oral progesterone replacement in postmenopausal women. The oral administration of progesterone, however, is compromised by individual differences in bioavailability and metabolism of the steroid. Objective: We compared the sleep-endocrine effects after intranasal progesterone (MPP22), zolpidem and placebo in healthy postmenopausal women. Design: This was a randomized double-blind cross-over study. Setting: German monocentric study Participants: Participants were 12 healthy postmenopausal women. Interventions: Subjects received in randomized order four treatments, 2 doses of intranasal progesterone (4.5 mg and 9 mg of MPP22), 10 mg of zolpidem and placebo. Outcome measures: Main outcome were conventional and quantitative sleep-EEG variables. Secondary outcomes were the subjective sleep variables and the sleep related concentrations of cortisol, growth hormone (GH), melatonin and progesterone. Results: Sleep promoting effects were found after the higher dosage of MPP22 and after zolpidem. Zolpidem prompted benzodiazepine-like effects on quantitative sleep EEG as expected, whereas no such changes were found after the two dosages of MP22. Nocturnal progesterone levels increased after 9.0 mg MPP22. No other changes of hormone secretion were found. Conclusions: Our study shows sleep promoting effects after intranasal progesterone. The spectral signature of intranasal progesterone did not resemble the sleep-EEG alterations induced by GABA active compounds. Progesterone levels were elevated after 9.0 mg MPP22. No other endocrine effects were observed.